MEAN web development workshop : LiveLessons - Wandschneider, Marc; Safari eBooks ([Place of publication not identified] : Addison-Wesley : Pearson, 2016)
"Recorded live at a workshop training session, MEAN Web Development Workshop allows you to sit in as expert trainer Marc Wandschneider covers the fundamentals of the MEAN stack MongoDB, Express, AngularJS, and Node.js while walking the workshop participants through the process of creating real-world web applications. The first section covers using Node.js to build the backend web server components, the next section covers using MongoDB as the data store for the Node.js backend components, and the final section covers using AngularJS as the client-side framework for the web application."--Resource description page.
Presenter, Marc Wandschneider.
Title from title screen (viewed June 15, 2016).
Keywords: Web site development; MongoDB; EXPRESS (Computer program language); AngularJS (Software framework); Node.js.; Electronic books